Iran awakening from prison to peace prize : one woman's struggle at the crossroads of history - ʻIbadi, Shirin (Rider, 2006)
Shirin Ebadi is an Iranian human rights lawyer and activist. She is known for defending dissident figures, and for the establishment of a number of non-profit grassroots organisations dedicated to human rights. In 2003, she became the first Muslim woman, and the first Iranian, to be awarded the Nobel Peace Prize. Here, she tells her story.